2013
DOI: 10.1016/j.talanta.2013.03.086
|View full text |Cite
|
Sign up to set email alerts
|

Determination of PCDD/Fs, PBDD/Fs and dioxin-like PCBs in human milk from mothers residing in the rural areas in Flanders, using the CALUX bioassay and GC-HRMS

Abstract: Since the CALUX (Chemically Activated LUciferase gene eXpression) bioassay is a fast and inexpensive tool for the determination of dioxin-like compounds in a large number of samples and requires only small sample volumes, the use of this technique in human biomonitoring programs provides a good alternative to GC-HRMS. In this study, a new CALUX method for the separate analysis of PCDD/Fs and dioxin-like PCBs (dl-PCBs) in small amounts of human milk samples with the new sensitive H1L7.5c1 cell line was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The more abundant congeners were 2, 3,7,3,4,7,3,7,3,7, were also noted at comparatively high levels. A PBDD/F TEQ of 0.67 ng/kg lipid was reported (Colles et al, 2008) for a pooled milk sample from Belgian mothers, and a later, pooled Belgian milk sample from Flanders (Croes et al, 2013) reported a TEQ of 0.42 or 0.34 pg/g lipid, depending on whether TEF 1998 or TEF 2005 was used. Similar concentrations (0.45 to 2.64 pg TEQ /g lipid) and a similar frequency of occurrence of 2,3,7,8-TBDF and 2,3,4,7,8-PeBDF as the Japanese study, were seen in 31 pooled breast milk samples from 25 countries (Asia-Pacific, Europe and North/South America), (Kotz et al, 2005;.…”
Section: Human Milkmentioning
confidence: 99%
“…The more abundant congeners were 2, 3,7,3,4,7,3,7,3,7, were also noted at comparatively high levels. A PBDD/F TEQ of 0.67 ng/kg lipid was reported (Colles et al, 2008) for a pooled milk sample from Belgian mothers, and a later, pooled Belgian milk sample from Flanders (Croes et al, 2013) reported a TEQ of 0.42 or 0.34 pg/g lipid, depending on whether TEF 1998 or TEF 2005 was used. Similar concentrations (0.45 to 2.64 pg TEQ /g lipid) and a similar frequency of occurrence of 2,3,7,8-TBDF and 2,3,4,7,8-PeBDF as the Japanese study, were seen in 31 pooled breast milk samples from 25 countries (Asia-Pacific, Europe and North/South America), (Kotz et al, 2005;.…”
Section: Human Milkmentioning
confidence: 99%
“…This tendency has been observed in other studies in which environmental samples have been analyzed using both bioanalytical and chemical methods (USEPA 2007;Tomoaki et al 2008;Masakazu et al 2009;Samara et al 2010;Croes et al 2012Croes et al , 2013. In immunoassay systems, some false positive interference for the lower concentration samples could be attributed to the presence of high levels of congeners that have significant EIA cross-reactivity but are not determined by the HRGC/HRMS analysis because they contribute minimal toxicity.…”
Section: Resultsmentioning
confidence: 54%
“…The second step is to purify the fat extract through the passage 6.73 pg OMS-PCDD/F-TEQ/g fat. The results obtained from the determination of the other samples show very low levels of contamination from 1.36 to 0.0054 µg OMS-PCDD/F-TEQ/g by demonstrating that the milk produced is a safe food for human consumption (see also Schuhmacher et al, 2002;Gullet & Touai, 2003;Croes et al, 2013).…”
Section: Methodsmentioning
confidence: 99%